A test of the evolutionary explanation of jealousy in the United States and Croatia - Mellgren, Roger L. (Array, 2010)
Numerous investigators reported results which support the evolutionary theory of sex differences in jealousy. In this study we extend the cross cultural evaluation of jealousy to a comparison between U.S. and Croatian populations. Two alternative forced choice methods were used to assess how upset males and females were in the sexual or emotional infidelity of their mate with either a same sex person (homosexual relationship) or an opposite sex person (heterosexual relationship). A checklist of emotions was also given to the subjects to assess in more detail their feelings about the infidelities. In both the US and Croatia females showed a strong tendency to be upset by the emotional infidelity in the heterosexual case, but a complete reversal to the sexual infidelity in the homosexual case. Males were more upset by the sexual infidelity than females in the heterosexual case, but less upset by the sexual infidelity than the females in the homosexual case. Self reported emotions revealed anger, disgust and sadness to differentiate the feelings of the subjects to the different situations. The Croatian participants reported significantly more emotions than the US participants. The general predictions of the evolutionary account of sex differences in what caused the most distress were supported.